Effectiveness of deep breathing and walking exercise in reducing menopausal symptoms among post-menopausal women of Tripura, India - Deb, Koyel; Gurumayum, Dolly (International Journal Of Community Medicine And Public Health, 2021)
Background: Menopause is the part of women’s life. Menopausal symptoms refer any feeling of illness or physical or mental change caused by menopause. Purpose of the study; to evaluate the effectiveness of deep breathing and walking exercise in reducing menopausal symptoms among post-menopausal women in selected community, Tripura and to find out the association between the pre-test menopausal symptoms among post-menopausal women with their selected demographic variables. Methods: A quantitative Quasi experimental research approach with short interrupted time series study design was used. The researcher selected 40 post-menopausal women as a sample by non-probability sampling technique. Data were collected with structured interview schedule on symptoms checklist and deep breathing and walking exercise practice checklist. Results: The study results show that the pre-observation of post-menopausal symptoms in the experimental group were; 12 (60%) post-menopausal women belong to Moderate group, 8 (40%) belong to severe group and nobody belong to mild group. Post-observation of post-menopausal symptoms of the experimental group were; 1(5%) post-menopausal woman belong to mild, 19 (95%) belong to moderate group and nobody belong to severe group. The pre-observation of post-menopausal symptoms in the control group were; post-menopausal women belong to Mild, Moderate and Severe group were 2 (10%), 13 (65%) and 5 (25%) respectively. Post-observation of post-menopausal symptoms of the control group were; 2 (10%) post-menopausal women belong to mild, 15 (75%) belong to moderate and 3 (15%) belong to severe group. Conclusions: The finding of present study revealed that breathing and walking exercise improved the post-menopausal symptoms in experimental group.